An Energy Efficient Task Scheduling for a Cloud-edge System. Issue 1 (1st February 2023) - Cheng, Xinyun; Yu, Jinghang; Zhang, Mingming; Xia, Fei; Zhang, Zichen; Ji, Mingtao
Abstract: With the widespread popularity of edge computing, the energy consumption of edge devices has attracted lots of research interests. This paper studies the cloud-edge system under the solar energy supply scenario, and optimizes the system parameter configuration according to the energy supply of photovoltaic power generation, to reduce the system energy consumption and prolong the system running time. Specifically, we built an edge video detection system based on Raspberry Pi, and deeply analyzed the energy consumption model of the system. Based on this, the problem of dynamically adjusting the video detection operating parameters is modeled as a long-term optimization problem. In order to solve this problem effectively, the long-term optimization problem is transformed to an instantaneous optimization problem, so that the problem can be solved efficiently in real time, and the rationality of this transformation is proved. Finally, we propose a low-energy-consumption scheduling algorithm to optimize the task scheduling and energy consumption of the system. Through simulation experiments, the performance of the proposed algorithm is evaluated. The results show that the scheduling algorithm can reduce the energy consumption of the system by an average of 18%.